Demagnetization studies in the North Singhbhum Mobile Belt, Eastern India: new palaeomagnetic poles, tectonics, and GRM - Chatterjee, Saurodeep; Mondal, Supriya; Basavaiah, N; Gain, Debesh; Das, Solanky (My University, 2022)
The present study deals with the alternating field (AF) demagnetization of the volcanic rocks and meta-sediments from the North Singhbhum Mobile Belt (NSMB) within a field of 2.5 to 100 mT. All the three rock types encountered were subjected to AF demagnetization and the behavior during demagnetization was noted. As the rocks of the NSMB have variable potential to record remanences, the samples to demagnetize were sorted based on their feasibility to record characteristic remanent magnetization (ChRM). A gradual decrease in the magnetic intensity of the quartzites during AF demagnetization yielded two stable palaeomagnetic vectors recorded in them. Two palaeomagnetic poles are determined from these stable vectors. The palaeomagnetic poles thus obtained from the quartzites lie on a hairpin bend in the Proterozoic apparent polar wandering path (APWP) of the Indian subcontinent. This is significant towards the ~ 1850 Ma initiated Satpura orogeny which developed the regional mesoscopic as well as the magnetic fabrics in the NSMB. Thus, these palaeomagnetic poles are useful in relating the regional tectonics and magneto-tectonics of the NSMB. However, the magnetic intensity of the schists and volcanic rocks continues to decrease with increasing applied AF up to a certain extent, and then again continues to increase, which proves that these samples are affected by the acquisition of gyro remanent magnetization (GRM), which is a magnetic vector component acquired by certain rocks during AF demagnetization of their natural remanent magnetization (NRM). As GRM is an imperfection commonly associated with AF demagnetization of the rocks, the samples with such features are not considered for tectonics-related palaeomagnetic studies in the NSMB.
Keywords: Alternating field; Demagnetization; GRM; Hairpin bend; NSMB; Palaeomagnetic poles; Tectonics